Interface interaction of transition metal phthalocyanines with strontium titanate (100) - Karstens, Reimer; Chassé, Thomas; Peisert, Heiko (Beilstein Journal of Nanotechnology, 2021)
We study interface properties of CoPcFx and FePcFx (x = 0 or 16) on niobium-doped SrTiO3(100) surfaces using mainly X-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy. For all studied molecules, a rather complex, bidirectional charge transfer with the oxide substrate was observed, involving both the macrocycle and the central metal atom. For molecules of the first monolayer, an electron transfer to the central metal atom is concluded from transition metal 2p core level photoemission spectra. The number of interacting molecules in the first monolayer on the oxide surface depends on the central metal atom of the phthalocyanine, whereas the substrate preparation has minor influence on the interaction between CoPc and SrTiO3(100). Differences of the interaction mechanism to related TiO2 surfaces are discussed.
Keywords: charge transfer at interfaces; strontium titanate; transition metal phthalocyanines

(untitled) - Grätzel, M. (J. Photochem. Photobiol., C, 2003)

(untitled) - Koch, N. (ChemPhysChem, 2007)

(untitled) - Diebold, U. (Surf. Sci. Rep., 2003)

(untitled) - Karamat, S.; Ke, C.; Inkaya, U. Y.; Akram, R.; Yildiz, I.; Zaman, S. S.; Oral, A. (Prog. Nat. Sci.: Mater. Int., 2016)

(untitled) - Sato, N.; Harada, Y.; Terashima, T.; Kanda, R.; Takano, M. (Appl. Surf. Sci., 2005)

(untitled) - Yang, Y.-C.; Xu, L.; Huang, W.-Q.; Luo, C.-Y.; Huang, G.-F.; Peng, P. (J. Phys. Chem. C, 2015)

(untitled) - Yadav, S.; Ghosh, S. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Yan, H.; Jo, T.; Okuzaki, H. (Jpn. J. Appl. Phys., 2010)

(untitled) - Mahmoud, W. E. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Kalappattil, V.; Geng, R.; Liang, S. H.; Mukherjee, D.; Devkota, J.; Roy, A.; Luong, M. H.; Lai, N. D.; Hornak, L. A.; Nguyen, T. D.; Zhao, W. B.; Li, X. G.; et al. (J. Sci.: Adv. Mater. Devices, 2017)

(untitled) - van Benthem, K.; Elsässer, C.; French, R. H. (J. Appl. Phys., 2001)

(untitled) - Kawasaki, M.; Takahashi, K.; Maeda, T.; Tsuchiya, R.; Shinohara, M.; Ishiyama, O.; Yonezawa, T.; Yoshimoto, M.; Koinuma, H. (Science, 1994)

(untitled) - Hatch, R. C.; Choi, M.; Posadas, A. B.; Demkov, A. A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2015)

(untitled) - Connell, J. G.; Isaac, B. J.; Ekanayake, G. B.; Strachan, D. R.; Seo, S. S. A. (Appl. Phys. Lett., 2012)

(untitled) - Koster, G.; Kropman, B. L.; Rijnders, G. J. H. M.; Blank, D. H. A.; Rogalla, H. (Appl. Phys. Lett., 1998)

(untitled) - Koo, B.; Kim, K.; Kim, J. K.; Kwon, H.; Han, J. W.; Jung, W. (Joule, 2018)

(untitled) - Kubo, T.; Nozoye, H. (Phys. Rev. Lett., 2001)

(untitled) - Szot, K.; Speier, W.; Breuer, U.; Meyer, R.; Szade, J.; Waser, R. (Surf. Sci., 2000)

(untitled) - Chambers, S. A.; Sushko, P. V. (Phys. Rev. Mater., 2019)

(untitled) - Iwaya, K.; Shimizu, R.; Ohsawa, T.; Hashizume, T.; Hitosugi, T. (Phys. Rev. B, 2011)

(untitled) - Hikita, T.; Hanada, T.; Kudo, M.; Kawai, M. (J. Vac. Sci. Technol., A, 1993)

(untitled) - Ohnishi, T.; Shibuya, K.; Lippmaa, M.; Kobayashi, D.; Kumigashira, H.; Oshima, M.; Koinuma, H. (Appl. Phys. Lett., 2004)

(untitled) - Bachelet, R.; Sánchez, F.; Palomares, F. J.; Ocal, C.; Fontcuberta, J. (Appl. Phys. Lett., 2009)

(untitled) - Fragneto, A.; De Luca, G. M.; Di Capua, R.; Scotti di Uccio, U.; Salluzzo, M.; Torrelles, X.; Lee, T.-L.; Zegenhagen, J. (Appl. Phys. Lett., 2007)

(untitled) - Kobayashi, D.; Hashimoto, R.; Chikamatsu, A.; Kumigashira, H.; Oshima, M.; Ohnishi, T.; Lippmaa, M.; Ono, K.; Kawasaki, M.; Koinuma, H. (J. Electron Spectrosc. Relat. Phenom., 2005)

(untitled) - Pancotti, A.; Barrett, N.; Zagonel, L. F.; Vanacore, G. M. (J. Appl. Phys., 2009)

(untitled) - Castell, M. R. (Surf. Sci., 2002)

(untitled) - Sánchez, F.; Ocal, C.; Fontcuberta, J. (Chem. Soc. Rev., 2014)

(untitled) - Peisert, H.; Knupfer, M.; Schwieger, T.; Fuentes, G. G.; Olligs, D.; Fink, J.; Schmidt, T. (J. Appl. Phys., 2003)

(untitled) - Brinkmann, H.; Kelting, C.; Makarov, S.; Tsaryova, O.; Schnurpfeil, G.; Wöhrle, D.; Schlettwein, D. (Phys. Status Solidi A, 2008)

(untitled) - Meiss, J.; Merten, A.; Hein, M.; Schuenemann, C.; Schäfer, S.; Tietze, M.; Uhrich, C.; Pfeiffer, M.; Leo, K.; Riede, M. (Adv. Funct. Mater., 2012)

(untitled) - Mayer, T.; Hunger, R.; Klein, A.; Jaegermann, W. (Phys. Status Solidi B, 2008)

(untitled) - Greulich, K.; Belser, A.; Bölke, S.; Grüninger, P.; Karstens, R.; Sättele, M. S.; Ovsyannikov, R.; Giangrisostomi, E.; Basova, T. V.; Klyamer, D.; Chassé, T.; Peisert, H. (J. Phys. Chem. C, 2020)

(untitled) - Schuster, B.-E.; Basova, T. V.; Plyashkevich, V. A.; Peisert, H.; Chassé, T. (Thin Solid Films, 2010)

(untitled) - Klyamer, D. D.; Sukhikh, A. S.; Krasnov, P. O.; Gromilov, S. A.; Morozova, N. B.; Basova, T. V. (Appl. Surf. Sci., 2016)

(untitled) - Sukhikh, A. S.; Klyamer, D. D.; Parkhomenko, R. G.; Krasnov, P. O.; Gromilov, S. A.; Hassan, A. K.; Basova, T. V. (Dyes Pigm., 2018)

(untitled) - de Oteyza, D. G.; El-Sayed, A.; Garcia-Lastra, J. M.; Goiri, E.; Krauss, T. N.; Turak, A.; Barrena, E.; Dosch, H.; Zegenhagen, J.; Rubio, A.; Wakayama, Y.; Ortega, J. E. (J. Chem. Phys., 2010)

(untitled) - Rückerl, F.; Waas, D.; Büchner, B.; Knupfer, M. (J. Electron Spectrosc. Relat. Phenom., 2017)

(untitled) - Peisert, H.; Uihlein, J.; Petraki, F.; Chassé, T. (J. Electron Spectrosc. Relat. Phenom., 2015)

(untitled) - Balle, D.; Adler, H.; Grüninger, P.; Karstens, R.; Ovsyannikov, R.; Giangrisostomi, E.; Chassé, T.; Peisert, H. (J. Phys. Chem. C, 2017)

(untitled) - Yeh, J. J.; Lindau, I. (At. Data Nucl. Data Tables, 1985)

(untitled) - Ballirano, P.; Caminiti, R.; Ercolani, C.; Maras, A.; Orrù, M. A. (J. Am. Chem. Soc., 1998)

(untitled) - Evangelisti, M.; Bartolomé, J.; de Jongh, L. J.; Filoti, G. (Phys. Rev. B, 2002)

(untitled) - Gould, R. D. (Coord. Chem. Rev., 1996)

(untitled) - Hesse, R.; Chassé, T.; Streubel, P.; Szargan, R. (Surf. Interface Anal., 2004)

(untitled) - Momma, K.; Izumi, F. (J. Appl. Crystallogr., 2011)

(untitled) - Palmgren, P.; Nilson, K.; Yu, S.; Hennies, F.; Angot, T.; Layet, J.-M.; Le Lay, G.; Göthelid, M. (J. Phys. Chem. C, 2008)

(untitled) - Sinha, S.; Islam, A. K. M. M.; Vorokhta, M.; Mukherjee, M. (J. Phys. Chem. C, 2017)

(untitled) - Ishida, N.; Fujita, D. (J. Phys. Chem. C, 2012)

(untitled) - Karstens, R.; Glaser, M.; Belser, A.; Balle, D.; Polek, M.; Ovsyannikov, R.; Giangrisostomi, E.; Chassé, T.; Peisert, H. (Molecules, 2019)

(untitled) - Raisch, C.; Chassé, T.; Langheinrich, C.; Chassé, A. (J. Appl. Phys., 2012)

(untitled) - Chassé, A.; Chassé, T. (J. Phys. Soc. Jpn., 2018)

(untitled) - Brena, B.; Luo, Y.; Nyberg, M.; Carniato, S.; Nilson, K.; Alfredsson, Y.; Åhlund, J.; Mårtensson, N.; Siegbahn, H.; Puglia, C. (Phys. Rev. B, 2004)

(untitled) - Peisert, H.; Knupfer, M.; Fink, J. (Synth. Met., 2003)

(untitled) - Petraki, F.; Peisert, H.; Biswas, I.; Chassé, T. (J. Phys. Chem. C, 2010)

(untitled) - Åhlund, J.; Nilson, K.; Schiessling, J.; Kjeldgaard, L.; Berner, S.; Mårtensson, N.; Puglia, C.; Brena, B.; Nyberg, M.; Luo, Y. (J. Chem. Phys., 2006)

(untitled) - Lukasczyk, T.; Flechtner, K.; Merte, L. R.; Jux, N.; Maier, F.; Gottfried, J. M.; Steinrück, H.-P. (J. Phys. Chem. C, 2007)

(untitled) - Schmid, M.; Kaftan, A.; Steinrück, H.-P.; Gottfried, J. M. (Surf. Sci., 2012)

(untitled) - Wang, J. Y.; Wang, J. Y.; Dougherty, D. B. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2020)

(untitled) - Glaser, M.; Peisert, H.; Adler, H.; Aygül, U.; Ivanovic, M.; Nagel, P.; Merz, M.; Schuppler, S.; Chassé, T. (J. Chem. Phys., 2015)

(untitled) - Toader, M.; Shukrynau, P.; Knupfer, M.; Zahn, D. R. T.; Hietschold, M. (Langmuir, 2012)

(untitled) - Petraki, F.; Peisert, H.; Uihlein, J.; Aygül, U.; Chassé, T. (Beilstein J. Nanotechnol., 2014)

(untitled) - Yu, J. C.; Yu, J. G.; Ho, W. K.; Jiang, Z. T.; Zhang, L. Z. (Chem. Mater., 2002)

(untitled) - Yu, J.; Xiang, Q.; Ran, J.; Mann, S. (CrystEngComm, 2010)

(untitled) - Schmidt, C.; Breuer, T.; Wippermann, S.; Schmidt, W. G.; Witte, G. (J. Phys. Chem. C, 2012)

(untitled) - Petraki, F.; Peisert, H.; Aygül, U.; Latteyer, F.; Uihlein, J.; Vollmer, A.; Chassé, T. (J. Phys. Chem. C, 2012)

(untitled) - Glaser, M.; Peisert, H.; Adler, H.; Polek, M.; Uihlein, J.; Nagel, P.; Merz, M.; Schuppler, S.; Chassé, T. (J. Phys. Chem. C, 2015)

(untitled) - Rauls, E.; Schmidt, W. G.; Pertram, T.; Wandelt, K. (Surf. Sci., 2012)

(untitled) - Belser, A.; Karstens, R.; Grüninger, P.; Nagel, P.; Merz, M.; Schuppler, S.; Suturina, E. A.; Chassé, A.; Chassé, T.; Peisert, H. (J. Phys. Chem. C, 2018)